Graphene and CNT filled hybrid thermoplastic composites for enhanced EMI shielding effectiveness. (17th May 2019) - Joseph, Jomy; Munda, Prithvi Raj; John, Dina A; Sidpara, Ajay M; Paul, Jinu
Abstract: Poly (methyl methacrylate) (PMMA)/multilayered graphene (MLG)/multi-walled carbon nanotubes (MWCNT) and Polyvinyl chloride (PVC)/MLG/MWCNT hybrid nanocomposites were prepared by solvent casting technique with four different filler weight fractions −20% MLG, 17.5%MLG + 2.5% MWCNT, 15% MLG + 5% MWCNT and 10%MLG + 10%MWCNT. Tensile properties and viscoelastic nature of the nanocomposites were studied as a function of the filler weight fraction. Hybrid composites exhibited either higher or almost same ultimate tensile strength and Young's modulus compared to MLG only composites. There has been a significant improvement in the electrical conductivity of the hybrid composites with 10 wt% MWCNT addition. Differential thermal analysis (DTA) of the composites shows improved thermal stability with increased MWCNT content. Multilayered hot stacked structures of the composites were prepared by hot compression technique and tested for their electromagnetic interference shielding effectiveness (EMI SE). A 2 mm hot stacked structure of both PVC/MLG/MWCNT and PMMA/MLG/MWCNT composites exhibited a maximum EMI SE of ∼43 dB in the X band frequency range.